Citrobacter freundii Activation of NLRP3 Inflammasome via the Type VI Secretion System. (5th November 2020) - Liu, Liyun; Song, Liqiong; Deng, Rong; Lan, Ruiting; Jin, Wenjie; Tran Van Nhieu, Guy; Cao, Huifang; Liu, Qin; Xiao, Yuchun; Li, Xianping; Meng, Guangxun; Ren, Zhihong
Abstract: Citrobacter freundii is a significant cause of human infections, responsible for food poisoning, diarrhea, and urinary tract infections. We previously identified a highly cytotoxic and adhesive C. freundii strain CF74 expressing a type VI secretion system (T6SS). In this study, we showed that in mice-derived macrophages, C. freundii CF74 activated the Nucleotide Oligomerization Domain -Like Receptor Family, Pyrin Domain Containing 3(NLRP3) inflammasomes in a T6SS-dependent manner. The C. freundii T6SS activated the inflammasomes mainly through caspase 1 and mediated pyroptosis of macrophages by releasing the cleaved gasdermin-N domain. The CF74 T6SS was required for flagellin-induced interleukin 1β release by macrophages. We further show that the T6SS tail component and effector, hemolysin co-regulation protein-2 (Hcp-2), was necessary and sufficient to trigger NLRP3 inflammasome activation. In vivo, the T6SS played a key role in mediating interleukin 1β secretion and the survival of mice during C. freundii infection in mice. These findings provide novel insights into the role of T6SS in the pathogenesis of C. freundii . Abstract : Citrobacter freundii type VI secretion system mainly activates the NLRP3-dependent caspase 1 signaling cascade that drives interleukin 1β production and mediates pyroptosis by releasing the cleaved gasdermin-N domain during C. freundii CF74 infection of macrophages.